2017
DOI: 10.1016/j.bpsc.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Default Mode Network Subsystems Are Differentially Disrupted in Posttraumatic Stress Disorder

Abstract: Background Posttraumatic stress disorder (PTSD) is a psychiatric disorder characterized by debilitating re-experiencing, avoidance, and hyperarousal symptoms following trauma exposure. Recent evidence suggests that individuals with PTSD show disrupted functional connectivity in the default mode network, an intrinsic network that consists of a midline core, a medial temporal lobe (MTL) subsystem, and a dorsomedial prefrontal cortex (dMPFC) subsystem. The present study examined whether functional connectivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 77 publications
(94 reference statements)
12
98
2
2
Order By: Relevance
“…Overall, consistent findings of reduced resting state functional connectivity between regions within the DMN in PTSD participants compared to controls has been emerging (Patel, Spreng, Shin, & Girard, ; Patriat, Birn, Keding, & Harringa, ; Sripada et al, ). PTSD participants with (Miler et al, ) and without mild traumatic brain injuries (Patriat et al, ; Sripada et al, ) have exhibited reduced connectivity between the hippocampus and prefrontal regions, such as the mPFC, compared to TEC (Jin et al, ; Spielberg, McGlinchey, Milberg, & Salat, ). This reduced within‐DMN connectivity may contribute to characteristic symptoms of PTSD such as intrusive memories, dissociation, or avoidance (Akiki, Averill, & Abdallah, ).…”
Section: Pavlovian Fear Learning and Memory In Post‐traumatic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, consistent findings of reduced resting state functional connectivity between regions within the DMN in PTSD participants compared to controls has been emerging (Patel, Spreng, Shin, & Girard, ; Patriat, Birn, Keding, & Harringa, ; Sripada et al, ). PTSD participants with (Miler et al, ) and without mild traumatic brain injuries (Patriat et al, ; Sripada et al, ) have exhibited reduced connectivity between the hippocampus and prefrontal regions, such as the mPFC, compared to TEC (Jin et al, ; Spielberg, McGlinchey, Milberg, & Salat, ). This reduced within‐DMN connectivity may contribute to characteristic symptoms of PTSD such as intrusive memories, dissociation, or avoidance (Akiki, Averill, & Abdallah, ).…”
Section: Pavlovian Fear Learning and Memory In Post‐traumatic Stressmentioning
confidence: 99%
“…This reduced within‐DMN connectivity may contribute to characteristic symptoms of PTSD such as intrusive memories, dissociation, or avoidance (Akiki, Averill, & Abdallah, ). PTSD participants with more severe avoidance and numbing symptoms had less functional connectivity within DMN, between the hippocampus and the posterior cingulate cortex (PCC), compared to TEC (Miler et al, ).…”
Section: Pavlovian Fear Learning and Memory In Post‐traumatic Stressmentioning
confidence: 99%
“…Recent work by Miller et al. () suggests that PTSD is associated with specific disruptions in the medial temporal lobe subsystem of the DMN, which includes regions such as the hippocampus and ventromedial prefrontal cortex. It is possible that the absence of a bivariate association between PTSD and DMN connectivity in the current study is related to this reported specificity of DMN alterations in PTSD, which was not tested here.…”
Section: Discussionmentioning
confidence: 99%
“…) and function (Miller et al . ). Therefore, we also examined the influence of PTSD and BDNF genotype to disentangle the contribution of this condition from mTBI‐related alterations in hippocampal volume.…”
mentioning
confidence: 97%